Endosomal pH is an evolutionarily conserved driver of phenotypic plasticity in colorectal cancer - Hari Prasad; Harshavardhan BV; Ayalur Raghu Subbalakshmi; Susmita Mandal; Mohit Kumar Jolly; Sandhya S. Visweswariah (npj Systems Biology and Applications)
Abstract Dysregulated pH is now recognised as a hallmark of cancer. Recent evidence has revealed that the endosomal pH regulator Na+/H+ exchanger NHE9 is upregulated in colorectal cancer to impose a pseudo-starvation state associated with invasion, highlighting an underexplored mechanistic link between adaptive endosomal reprogramming and malignant transformation. In this study, we use a model that quantitatively captures the dynamics of the core regulatory network governing epithelial mesenchymal plasticity. The model recapitulated NHE9-induced calcium signalling and the emergence of migratory phenotypes in colorectal cancer cells. Model predictions were compared with patient data and experimental results from RNA sequencing analysis of colorectal cancer cells with stable NHE9 expression. Mathematical analyses identified that tumours leverage elevated NHE9 levels to delay the transition of cells to a mesenchymal state and allow for metastatic progression. Ectopic expression of NHE9 is sufficient to induce loss of epithelial nature but does not fully couple with gain of mesenchymal state, resulting in a hybrid epithelial-mesenchymal population with increased aggressiveness and metastatic competence. Higher NHE9 expression is associated with cancer cell migration, and the effect appears to be independent of hypoxia status. Our data suggests that alterations in endosomal pH, an evolutionarily conserved starvation response, may be hijacked by colorectal cancer cells to drive phenotypic plasticity and invasion. We propose that cancer cells rewire their endosomal pH not only to meet the demands of rapid cell proliferation, but also to enable invasion, metastasis, and cell survival. Endosomal pH may be an attractive therapeutic target for halting tumour progression.